TYPOLOGY OF SOCIO-EMOTIONAL COMPETENCIES OF ELEMENTARY SCHOOL TEACHERS: ANALYSIS OF CHARACTERISTICS AND RESILIENCE IN LEARNING - haryanto; ngurah ayu nyoman murniati; Supandi (SOSIOEDUKASI, 2026)
The background of this research is the disconnect between the high psychological well-being of teachers and the decline in the quality of student learning in literacy and numeracy aspects in rural elementary schools. This qualitative case study research aims to dissect the typology of social-emotional competencies (SECs) of teachers at SDN Rajek, Grobogan Regency, to understand the disparity in cognitive achievement. Data were collected through observation, in-depth interviews, and a review of the 2024-2025 Education Report Card documents. The results revealed that the majority of teachers fall into the "Reflective-Stagnant" profile, where personal emotional maturity has not yet transformed into effective instructional resilience. The findings indicate that teacher empathy tends to be passive towards students' sociogeographical barriers. This study recommends a behavioral intervention matrix to shift teacher typology towards the "Resilient-Accelerative" profile through the integration of diagnostic SECs to restore the quality of learning in rural areas.